The Role Of Chatbots In Tobacco Cessation: A Scoping Review Of Applications, Benefits, And Challenges - Alkhudhairy, Rama A; Gaikwad, Rahul N; Aljubua, Reema H; Alharbi, Amjad M (Journal of Neonatal Surgery, 2025)
Background: Tobacco use remains a leading global health challenge, contributing significantly to morbidity and mortality. In the evolving field of digital health, chatbots have emerged as promising tools to support smoking cessation through behavior change communication, personalized intervention, and scalable outreach. However, the evidence base surrounding their real-world effectiveness and implementation barriers remains scattered. This scoping review explores how chatbots are used in tobacco cessation efforts, synthesizing current literature on their application, benefits, and limitations. It further examines the influence of artificial intelligence (AI), particularly generative large language models, in enhancing chatbot-driven smoking cessation interventions. Methods: Following Arksey and O’Malley’s methodological framework, we reviewed empirical studies, systematic reviews, and grey literature from 2019 to 2025 across databases including PubMed, Scopus, and IEEE Xplore. Studies were included if they assessed chatbot-based tobacco cessation interventions or user interactions in digital cessation environments. Results: A total of 14 relevant studies were analyzed. Applications ranged from rule-based SMS cessation bots to AI-enhanced generative platforms like ChatGPT. Reported benefits include 24/7 accessibility, anonymity, tailored motivation, and improved cessation engagement among adolescents and underserved populations. Key limitations include inconsistent efficacy, empathy deficits, overreliance risk, and concerns around privacy, misinformation, and regulatory oversight. Conclusion: Chatbots are poised to revolutionize tobacco cessation efforts through personalized, scalable digital interventions. However, robust evidence, particularly on AI-driven chatbots, remains limited. Future research should focus on real-world evaluation, clinical integration, and ethical safeguards to optimize outcomes.